Peptide methionine sulfoxide reductase from Escherichia coli and Mycobacterium tuberculosis protects bacteria against oxidative damage from reactive nitrogen intermediates - John, Gregory St. (National Academy of Sciences, 2001)
Inducible nitric oxide synthase (iNOS) plays an important role in host defense. Macrophages expressing iNOS release the reactive nitrogen intermediates (RNI) nitrite and S-nitrosoglutathione (GSNO), which are bactericidal in vitro at a pH characteristic of the phagosome of activated macrophages. We sought to characterize the active intrabacterial forms of these RNI and their molecular targets. Peptide methionine sulfoxide reductase (MsrA; EC 1.8.4.6) catalyzes the reduction of methionine sulfoxide (Met-O) in proteins to methionine (Met). E. coli lacking MsrA were hypersensitive to killing not only by hydrogen peroxide, but also by nitrite and GSNO. The wild-type phenotype was restored by transformation with plasmids encoding msrA from E. coli or M. tuberculosis, but not by an enzymatically inactive mutant msrA, indicating that Met oxidation was involved in the death of these cells. It seemed paradoxical that nitrite and GSNO kill bacteria by oxidizing Met residues when these RNI cannot themselves oxidize Met. However, under anaerobic conditions, neither nitrite nor GSNO was bactericidal. Nitrite and GSNO can both give rise to NO, which may react with superoxide produced by bacteria during aerobic metabolism, forming peroxynitrite, a known oxidant of Met to Met-O. Thus, the findings are consistent with the hypotheses that nitrite and GSNO kill E. coli by intracellular conversion to peroxynitrite, that intracellular Met residues in proteins constitute a critical target for peroxynitrite, and that MsrA can be essential for the repair of peroxynitrite-mediated intracellular damage.